How to govern business services exchanges: Contractual and relational issues - Vandaele, Darline; Rangarajan, Deva; Gemmel, Paul; Lievens, Annouk (International journal of management reviews : IJMR, 2007)
With firms concentrating on core competencies, more emphasis has been placed on outsourcing and dealing with external sourcing agents. This has led to a stronger academic focus on buyer–seller exchanges and the corresponding mechanisms for governing these exchanges. This paper gives an overview of previous research investigating the exchange governance phenomenon based on transaction cost theory or co‐operative interorganizational relationships. The results reveal that few research studies have investigated the overall picture of exchange governance, including both contractual and relational governance and taking into account antecedents as well as performance outcomes of the governance mechanisms involved. Moreover, despite the service‐dominant logic shift, limited attention is given to specific service characteristics and their impact on exchange governance. This paper attempts to meld economic and social related antecedents into a model with regard to exchange governance in business services settings. Contractual and relational governance issues and their impact on performance outcomes are also considered. The resulting model indicates that to govern business services exchanges efficiently, more emphasis should be placed on behavioral uncertainty, human and process asset specificity and contractual governance. The paper concludes by discussing several directions for future research.